Multispacer Sequence Typing for Mycobacterium bovis Genotyping - Sales, Érica Bravo; Fonseca, Antônio Augusto; Gonçalves, Cristina Magalhães; Lage, Andrey Pereira; Andrade, Giovanna Ivo; Suffys, Philip Noel; Gomes, Harrison Magdinier; Dias, Natanael Lamas; Ferreira Neto, José Soares; Guimarães, Ana Marcia de Sá; Heinemann, Marcos Bryan (Frontiers in Veterinary Science, 2021)
The molecular typing of Mycobacterium bovis, which causes bovine tuberculosis, can be accomplished by combining different polymorphic markers, contributing to its epidemiological investigation. Multispacer sequence typing (MST) is a sequencing-based method that employs intergenic regions susceptible to higher mutation rates given the low selection pressure. It has been applied to M. tuberculosis, but not to M. bovis. The aim of this study was to evaluate a MST for M. bovis. A total of 58 strains isolated from tissues with lesions suggestive of bovine tuberculosis, coming from cattle herds in six Brazilian states and four standard samples of M. bovis were typified employing the MST technique. Fourteenintergenic regions were used and four types of genetic events were reported: single nucleotide mutation (SNP), insertion, deletion and tandem repeat (TR). Seven loci were chosen for typing. The result allowed the identification of 28 type sequences (ST), indicating a 92.9% HGDI. The data were used to analyze the evolutionary patterns of these isolated and correlate them to phylogeographic lineages based on the formation of clonal complexes generated from eBURST software. Later, we associate the MST with spoligotyping technique, currently considered the gold standard for classification of M. bovis. The results support the MST as an alternative method for genotyping of M. bovis. The method has the advantage of sequencing and the availability of sequences analyzed in public databases, which can be used by professionals around the world as a tool for further analysis.